Procedure of Reading and Calculation of Volt-Ampere and Current Transformer Magnetization Characteristics on the Basis of Digital Technologies - V. Kh. Sopyanik; A. I. Vlasov; E. A. Gloushonok; V. L. Radiuok (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper reveals the procedure of reading and calculation of operational, average and amplitude volt-ampere and current transformer magnetization characteristics with the help of a portable digital oscillograph.